Current Location  >  Math Formulas > Calculus > Differentiation Rules

Differentiation Rules

Chain Rule

Inverse Function

, where c is a constant

Product Rule

Quotient Rule

Reciprocal Rule

Differentiation of Implicit Functions
If an equation is expressed as y = f(x), then y is said to be the explicit function of x. However if y is connected with x by an expression f (x, y) = 0, then y is said to an implicit function of x. For e.g. x2 + 3xy + y2 = 0.

For differentiating the implicit function we differentiate each term with respect to x keeping in mind that if there is a term contains powers of y, we differentiate first with respect to y and then multiply it by
dy/dx to get its differentiation with respect to x.

Example 1:

Example 2: Calculate dy/dx for x3-3y2=21
Differentiating both side of equation with respect to x, and using The Sum Rule:

Now using The Chain Rule which leads to:

Example 3: Differentiate

Recall that D{ax} = axlna

Recall that axax = ax+x = a2x and axbx = (ab)x

Recall that lnA – lnB = ln(A/B)


Example 4: Differentiate

Factor 2x and (x2 – 1)2 from the numerator © 2018 | Contact us | Terms of Use | Privacy Policy | Yellow Sparks Network
Web Formulas